PENGAWASAN KANTOR WILAYAH KEMENTERIAN AGAMA PROVINSI RIAU TERHADAP PENYELENGGARA PERJALANAN IBADAH UMRAH (PPIU) DI KOTA PEKANBARU TAHUN 2018 - Winda Resti; M. Y. Tiyas Tinov (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Umrah pilgrimage tour is a series of umrah pilgrimage activities that include service development and congregational protection carried out by the ministry or umrah travel organizers. The regional Office of the Ministry of Religion has the task of providing guidance an in the implementation of umrah pilgrimage, the regional Office of the Ministry of Religion at the Provincial level is involved in the process of monitoring the implementation of umrah pilgrimage at the Provincial level. But what is happening today is that there are still many umrah travel agents who ceat to get big profits. Therefore, the Ministry of Religion of Riau Province must increase supervision so that it can be controlled from irregularities in the Umrah Pilgrimage. The formulation taken is how to supervise the Regional Office of the Ministry of Religion of Riau Province on the organizers of umrah pilgrimages in Pekanbaru City in 2018.            The purpose of the study was to determine the supervision of the Regional Office of the Ministry of Religional of Riau Province on the organizers ofUmrah Pilgrimage in Pekanbaru City 2018. The research method used is qualitative research. This type of research is descriptive qualitative, the research location is at the Regional Office of the Ministry of Religion of Riau Province and travel agents for umrah pilgrimage. Data collection techniques by means of interviews and documentation studies. Data analysis technique by using qualitative data analysis or exposure and description in words or sentences of data that has been obtained to obtain conclusions.            The results of the study indicate that the ministry of religion of riau province has not maximally supervised umrah travel agents so that there are still many umrah travel agents who commit fraud. This monitoring is carried out twice a year. The form supervised by the ministry of religion of riau province is registration, of financial management, travel plans, operational activities, congregational service, management and use of visas, indication of irregularities or certain cases and compliance with statutory provisions.Keywords: Control, Umrah Worship, Umrah Pilgrimage Trip, Umrah Travel Organizer